Modelling the spread and connectivity of waterborne marine pathogens: the case of PaV1 in the Caribbean. (21st November 2014) - Kough, Andrew S.; Paris, Claire B.; Behringer, Donald C.; Butler, Mark J.
Abstract: The PaV1 virus infects spiny lobsters ( Panulirus argus ) throughout most of the Caribbean, where its prevalence in adult lobsters can reach 17% and where it poses a significant risk of mortality for juveniles. Recent studies indicate that vertical transmission of the virus is unlikely and PaV1 has not been identified in the phyllosoma larval stages. Yet, the pathogen appears subclinically in post-larvae collected near the coast, suggesting that lobster post-larvae may harbour the virus and perhaps have aided in the dispersal of the pathogen. Laboratory and field experiments also confirm the waterborne transmission of the virus to post-larval and early benthic juvenile stages, but its viability in the water column may be limited to a few days. Here, we coupled Lagrangian modelling with a flexible matrix model of waterborne and post-larval-based pathogen dispersal in the Caribbean to investigate how a large area with complex hydrology influences the theoretical spread of disease. Our results indicate that if the virus is waterborne and only viable for a few days, then it is unlikely to impact both the Eastern and Northwestern Caribbean, which are separated by dispersal barriers. However, if PaV1 can be transported between locations by infected post-larvae, then the entire Caribbean becomes linked by pathogen dispersal with higher viral prevalence in the North. We identify possible regions from which pathogens are most likely to spread, and highlight Caribbean locations that function as dispersal "gateways" that could facilitate the rapid spread of pathogens into otherwise isolated areas.